2004
DOI: 10.1186/cc2877
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin and C-reactive protein during systemic inflammatory response syndrome, sepsis and organ dysfunction

Abstract: Introduction Both C-reactive protein (CRP) and procalcitonin (PCT) are accepted sepsis markers. However, there is still some debate concerning the correlation between their serum concentrations and sepsis severity. We hypothesised that PCT and CRP concentrations are different in patients with infection or with no infection at a similar severity of organ dysfunction or of systemic inflammatory response. Patients and methods One hundred and fifty adult intensive care unit patients were observed consecutively ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
88
2
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(107 citation statements)
references
References 38 publications
12
88
2
5
Order By: Relevance
“…1 Although it is considered a non-specific biomarker, research has suggested that patients with an elevated base level of CRP are at a higher risk of diabetes, 2 sepsis, 3 and most importantly, cardiovascular disease. 4 Thus, monitoring CRP levels is considered a useful method of screening and disease management.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although it is considered a non-specific biomarker, research has suggested that patients with an elevated base level of CRP are at a higher risk of diabetes, 2 sepsis, 3 and most importantly, cardiovascular disease. 4 Thus, monitoring CRP levels is considered a useful method of screening and disease management.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, 86 studies were included after two updated searches in February 2015 and September 2016 (Fig. 1) (Abidi et al 2008; Ahmadinejad et al 2009; Al-Nawas et al 1996; Anand et al 2015; Balc et al 2003; Barati et al 2010; Battista et al 2016; Bell et al 2003; Beqja-Lika et al 2013; Carpio et al 2015; Castelli et al 2004; Clec’h et al 2006; de Pablo et al 2013; Dorizzi et al 2006; Du et al 2003; Endo et al 2012; Farag et al 2013; Feng et al 2012; Gaini et al 2006; Garnacho-Montero et al 2014; Gerrits et al 2013; Giamarellos-Bourboulis et al 2008; Gibot et al 2004; Godnic et al 2015; Guven et al 2002; Han et al 2016; Harbarth et al 2001; Hoenigl et al 2013; Hou et al 2012, 2016; Hsu et al 2011; Ishikura et al 2014; Ivancevic et al 2008; Jekarl et al 2013, 2014; Jiang et al 2015; Kim and Zhang 2012; Kofoed et al 2007; Latour-Perez et al 2010; Lewis et al 2015; Li et al 2013a; Lin et al 2015; Matera et al 2013; Mat-Nor et al 2016; Mearelli et al 2014; Meynaar et al 2011; Miglietta et al 2015; Miller et al 1999; Muthiah et al 2007, Naeini and Montazerolghaem 2006; Oshita et al 2010; Papadimitriou-Olivgeris et al 2015; Ratzinger et al 2013; Reichsoellner et al 2014; Righi et al 2014; Rivera-Chavez and Minei 2009; Rogina et al 2014; Romualdo et al 2014; Ruiz-Alvarez et al 2009; Sakr et al 2008; Scherpereel et al 2006; Schulte et al 2011; Selberg et al 2000; Seok et al 2012; Shozushima et al 2011; Sierra et al 2004; Su et al 2012, 2013; Sungurtekin et al …”
Section: Resultsmentioning
confidence: 99%
“…This study results concluded that there were significant differences between PCT concentration and the sepsis severity by Mann Whitney test obtained p <0,05. [26] Jeong et al in 2012 explained that PCT concentrations was higher in septic patients than in non-sepsis patients with ratio concentration ratio of 3.2 ng/ml compared to 0.4 ng/ml. [27] Similar results were also obtained by Dorrizi et al 2006 that the PCT concentration in sepsis patients is higher than in non-sepsis treated in the ICU and inpatient with each PCT concentration ratio of 3.18 ng/mL and 0.45 ng/ml.…”
Section: Discussionmentioning
confidence: 99%